Awareness on Diabetes Complications among Clients at a University Hospital, Kathmandu - Paudel, Kalpana (Journal of Nursing Education of Nepal, 2023)
Introduction: Diabetes mellitus appears to be a global major non-communicable disease threatening both developed and developing countries including Nepal. The study aimed to assess an awareness regarding complications of diabetes mellitus among respondents visiting the diabetes clinic at a University Hospital Kathmandu Nepal. Methods: A descriptive study design was carried out among 100 respondents attending medical out patients department of a university hospital, Nepal. Non-probability purposive sampling technique was used to select the sample. Structured interview questionnaire was used to obtain information such as socio-demographic, disease related and awareness on complications of diabetes. Descriptive statistics was used for data analysis. Results: The result showed that diabetes mellitus is common in female (60) and above 60 years (46) where 33% had positive family history having diabetes. Majorities (84%)of them believed that diabetes had complications where 54% respondents were aware about hyperglycaemia followed by hypoglycaemia (33%), whereas only 24% and 21%of respondents were aware on limbs and heart problems caused by diabetes respectively. Regarding the preventive measure of diabetes complications, only 45%, 43%, 7%, 5% and 3% of respondents were aware on need of diet management, regular exercise, regular check-up, self-monitoring of blood glucose and self-care of foot after having diabetes. Conclusion: The findings concluded that diabetes clients have knowledge about the diabetes but they lack in-depth awareness on the various complications of diabetes and their preventive measures. Further expansion of diabetes education and awareness programs can be improved self-regulatory awareness of diabetes complications which may reduce the morbidity and premature death caused by diabetes mellitus.